Effects of formaldehyde catchers on emission of formaldehyde and dimensional stability of rubberwood particleboard - Lum, Wei Chen (2014)
Formaldehyde catcher, although, effective in reducing formaldehyde emission, affect the dimensional stability of particleboard produced. Dimensional instability is undesirable because the swelling process when exposed to water, functionally and visually, bring about gradual structural deterioration resulted in lower strength and degraded surface appearance. Thus, this study aimed to establish optimum processing parameters to work with this post-treatment and add-in formaldehyde catcher in order to produce particleboard with formaldehyde emission and properties particularly dimensional stability that comply with Japanese Industrial Standard. The processing parameters include different amount of particles used for surface layer and core layer (surface-to-core ratio), resin content, types of application method and the types of catcher used. Rubberwood was used as the main raw material in this study. Type E1 urea formaldehyde resin was used as the binder. Wax and hardener was also added to the resin. The code name for formaldehyde catcher applied on the surface of the boards after conditioning (post-treatment) was SF1188. On the other hand, formaldehyde catchers added into the adhesive mixture (add-in) were named as Catcher 1, Catcher 2 and Catcher 3 with the active ingredient amino compound, glycerol and melamine respectively. The tests for physical and mechanical properties were conducted in accordance with JIS A 5908:2003. Statistical analysis (ANCOVA or ANOVA) was carried out to determine the effects of the variables on the board’s properties. Pearson’s correlation was also been carried out to measure the strength of association between the studied variables and properties of particleboard. The results show that, particleboard produced using of 60% surface particles and 40% core particles had the highest Modulus of Rupture (MOR) and second lowest thickness swelling (TS) for the particleboard manufactured. Boards applied with the highest dosage of post-treatment formaldehyde catcher show a reduction of approximately 70% of formaldehyde emission. The lowest formaldehyde emission value for add-in formaldehyde catcher came from the boards applied with Catcher 1 (0.211 mg/L). Overall, particleboards applied with 60 gm-2 of post-treatment catcher and 6% of add-in catcher show the lowest formaldehyde emission, with the lowest value achieving 0.163 mg/L. Despite the low formaldehyde emission, these boards were in poor dimensional stability. Therefore, optimization was carried out by the application of heat treatment and the selection of specific mat moisture (3-11%) to impart better dimensional stability and lower formaldehyde emission upon the particleboard. Particleboards produced with 9% mat moisture show the lowest thickness TS value (11.67%). Heat treatment at 170 °C further reduced the TS value to 10.87%. Also, formaldehyde emission for samples treated at 170 °C successfully achieved Super E0 level. In conclusion, particleboards which complied with all criterions stated in JIS A 5908:2003 was successfully produced by the combination of formaldehyde catcher and dimensional improvement with careful selection of mat moisture and heat treatment.